2000
DOI: 10.1159/000026685
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Analysis of Antidepressant Drug Effects on the GABA<sub>A</sub> Receptor Complex Based upon Antagonist-Induced Encephalographic Power Spectrum Changes

Abstract: To better understand antidepressant drug effects on the GABAA receptor complex (the GABAA receptor, chloride ionophore and benzodiazepine receptor), we investigated how antidepressants influenced power spectrum changes induced by pentylenetetrazol (PTZ), a chloride ionophore antagonist, in the rat hippocampal electroencephalogram (EEG). In control recording, PTZ (27.5 mg/kg i.p.) increased EEG power at frequencies under 12 Hz up to five times. After rats were pretreated with imipramine, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…56,57 Recent studies in rats that examined the effects of antidepressants on GABA A receptors based on antagonist-induced EEG power spectrum changes suggest that imipramine may enhance the function of the GABA A receptor complex. 58 It is thus likely that some of the EEG effects of imipramine may be related to its GABA-ergic effects. Whether such properties are shared by amitriptyline as well remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Recent studies in rats that examined the effects of antidepressants on GABA A receptors based on antagonist-induced EEG power spectrum changes suggest that imipramine may enhance the function of the GABA A receptor complex. 58 It is thus likely that some of the EEG effects of imipramine may be related to its GABA-ergic effects. Whether such properties are shared by amitriptyline as well remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased GABA synthesis in amygdala, hippocampus, lateral septum after selective NE reuptake inhibitors [Herman et al, 2003]. Reduced pentylenetetrazoleactivated hippocampal electroencephalogram power in rats after AD treatment [Matsubara et al, 2000]. Recovery from depression increases plasma level of GABA-active steroid agonists allopregnanolone and pregnanolone but decreases concentration of steroid antagonist 3b-hydroxy5a-pregnan-20-one [Rupprecht, 2003].…”
Section: Historical Background and Recent Findingsmentioning
confidence: 99%
“…The pharmacological properties of GABARs are determined in large part by their subunit composition (Korpi et al, 2002). Previous studies have suggested both positive and negative regulation of GABAR activity by fluoxetine (Tunnicliff et al, 1999;Matsubara et al, 2000). However, there is little current evidence of a direct effect on the GABAR by fluoxetine or of the possible role of GABAR subunit composition in this modulation.…”
mentioning
confidence: 99%